The Manifestation of Real Norms and Ideal Norms among Muslims in Hamtramck - Rifka Pratama (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2017)
AbstractThis research aims at explaining life of and religious norms conformed by Muslims in Hamtramck, a predominantly Muslim city in Wayne County of the U.S. state of Michigan. More specifically, through this paper the writer tries to explain and analyze the norms conformed by Muslims in Hamtramck from a socio-cultural perspective. Based on the data the writer sees the existence of two forms of norms conformed by Muslims in their daily life in Hamtramck. Later, these norms are called ideal norms and real norms. In this research, the data is collected by using library study method. The data on the portrait of Muslims’ socio-cultural life in Hamtramck is obtained from newspaper articles and some video coverages. Furthermore, the data is processed and interpreted by using the theory that has been selected by the writer. The research suggests that the socio-cultural interaction of Muslims in Hamtramck is mostly based on the real norms while the ideal norms are conformed mostly in the context of religious rituals.Keywords: Manifestation; Ideal Norms; Real Norms; Muslims; Hamtramck.